Transportation Resilience under Climate Change: Infrastructure, Policy, Technology, and Social Dimensions - Andrianto, Deny Tomy; Zulkarnain, Ahnis; Yuliantini (Indonesian Scientific Publication, 2025)
Resilience in transportation systems is increasingly critical as climate change intensifies the frequency and severity of natural disasters. This study aimed to synthesize existing research on strategies that enhance transportation resilience by examining infrastructure, policy frameworks, technological innovations, and socio-economic conditions. A narrative review methodology was employed, with literature collected from Scopus, PubMed, and Google Scholar using targeted keywords such as transportation resilience, natural disasters, infrastructure resilience, and disaster recovery. Inclusion criteria emphasized peer-reviewed empirical and modeling studies published between 2010 and 2025 that directly addressed transportation resilience. The review finds that strengthening physical infrastructure through adaptive design, improved drainage, and advanced engineering reduces vulnerability to floods and earthquakes. Policy frameworks and inter-agency collaboration provide systemic coordination, while technological innovations—including Internet of Things, Artificial Intelligence, and digital twin simulations—significantly enhance predictive capacity and accelerate recovery operations. However, socio-economic disparities remain a central challenge, with developing nations facing extended recovery periods due to limited resources and fragile infrastructure. Cross-country comparisons underscore the importance of aligning resilience strategies with local contexts while promoting global knowledge exchange. Methodological limitations in the literature highlight the need for more interdisciplinary approaches that integrate technical, social, and policy dimensions. Overall, this review demonstrates that a multidimensional approach combining infrastructure reinforcement, governance reforms, technological innovation, and community engagement is essential to strengthen transportation resilience. These findings carry important implications for policymakers, practitioners, and researchers seeking to develop sustainable and adaptive transport systems in the face of escalating disaster risks.